Hungarian Monitoring, 8 July 1988 . [Magyar rádiófigyelő], 1988. július 8 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Situations in Yerevan and Karabakh - Warsaw Pact defense ministers' meeting in Moscow - Situation in Beirut Domestic Affairs: - Károly Grósz prepares for his tour of the US - Patriotic Popular Front debates rights to assemble and associate - Conference on Romania's village destruction plan - Bankruptcy procedure against Jurta theater - Interview with political scientists Máté Szabó - Premiere of Csurka's drama “To Stay”, interview with the author Külpolitika - A jereváni és karabahi helyzet - VSZ hadügyminisztereinek moszkvai ülése - Bejruti helyzet Belföld: - Grósz Károly Egyesült Államok-beli körútjának előkészületei - Vita a gyülekezési és egyesülési jogról a HNF-ban - Konferencia a román faluromboló programról - Csődeljárás a Jurta színház ellen - Interjú Szabó Máté politológussal - Csurka "Megmaradni" c. drámájának ősbemutatója: interjú a szerzővel